2019
DOI: 10.1002/stem.3128
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid receptor 4 regulates osteogenic and adipogenic differentiation of progenitor cells via inactivation of RhoA/ROCK1/β-catenin signaling

Abstract: Recent evidence revealed that lysophosphatidic acid receptor 4 (LPAR4) plays a role in osteogenesis and bone remodeling in mice. However, the molecular mechanism by which LPAR4 controls osteogenic and adipogenic differentiation of mesenchymal progenitor cells remains pending. In the current study, our data showed that Lpar4 was expressed in bone and adipose tissue and the expression increased during osteoblast and adipocyte differentiation. Lpar4 overexpression in stromal ST2 and preosteoblastic MC3T3‐E1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…We focused our attention on the RhoA signaling pathway as the increased level of RhoA was higher than the decreased level of Rac1. In addition, previous studies have proven that mediation of RhoA regulates proliferation and differentiation of mesenchymal stem cells [26][27][28][29], adipose-derived stem cells (ADSCs) [30], muscle stem cells [31], and a bulk of cancer cells [18,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…We focused our attention on the RhoA signaling pathway as the increased level of RhoA was higher than the decreased level of Rac1. In addition, previous studies have proven that mediation of RhoA regulates proliferation and differentiation of mesenchymal stem cells [26][27][28][29], adipose-derived stem cells (ADSCs) [30], muscle stem cells [31], and a bulk of cancer cells [18,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Cell lines represent at least some of the major characteristics of primary cells. The bone marrow-derived mesenchymal cell line ST2 can undergo osteogenic and adipogenic differentiation in vitro [ 39 , 40 ]. ST2 cells increase IL6 expression in response to prostaglandin E 2 exposure [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that ROCK1 and NFE2L1 could activate the activity of Wnt signaling pathway in human cancers. ROCK1 has been confirmed as the main gene of the Wnt signaling pathway (Mohammadi‐Yeganeh et al., 2019 ; Xie et al., 2020 ). The recent research also reported that NFE2L1 could regulate lung adenocarcinoma progression through Wnt pathway (Wei et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that NFE2L1was involved in SLCO4A1-AS1-mediated activation of WNT pathway and accelerated lung adenocarcinoma progression. In like manner, ROCK1 was confirmed as the main genes of the Wnt signaling pathway (Mohammadi-Yeganeh et al, 2019;Xie et al, 2020). Thus, we evaluated whether through upregulating ROCK1 and NFE2L1.…”
Section: Discussionmentioning
confidence: 99%